An approach to transgene expression in liver endothelial cells using a liposome‐based gene vector coated with hyaluronic acid. Issue 9 (7th March 2013) - Yamada, Yuma; Hashida, Masahiro; Hayashi, Yasuhiro; Tabata, Mai; Hyodo, Mamoru; Ara, Mst. Naznin; Ohga, Noritaka; Hida, Kyoko; Harashima, Hideyoshi; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; et al.
Abstract Dysfunctional sinusoidal liver endothelial cells (LECs) are associated with liver diseases, such as liver fibrosis, cirrhosis, and portal hypertension. Because of this, gene therapy targeted to LECs would be a useful and productive strategy for directly treating these diseases at the level of genes. Here, we report on the development of a transgene vector that specifically targets LECs. The vector is a liposome‐based gene vector coated with hyaluronic acid (HA). HA is a natural ligand for LECs and confers desirable properties on particles, rendering them biodegradable, biocompatible, and nonimmunogenic. In this study, we constructed HA‐modified carriers, and evaluated cellular uptake and transfection activity using cultured LECs from KSN nude mice (KSN–LECs). Cellular uptake analyses showed that KSN–LECs recognized the HA‐modified carriers more effectively than skin endothelial cells. The transfection assay indicated that the efficient gene expression in KSN–LECs, using the HA‐modified carriers, required an adequate lipid composition and a functional device to control intracellular trafficking. This finding contributes to our overall knowledge of transgene expression targeted to LECs. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3119–3127, 2013